The Analysis of Factors that Influence Students Choosing a Mechanical Engineering Education Study Program at Yogyakarta State University - Andrian Riyadi; Aulia Majid (VANOS Journal of Mechanical Engineering Education, 2024)
The Mechanical Engineering Education study program has students with various backgrounds, so the study program needs to identify why its students have various backgrounds, looking at the factors that influence them. The results of this identification are used as material for designing learning and marketing strategies to the community. The aim of this research is to find out what factors influence students in choosing a study program. The research method used is qualitative descriptive research using a questionnaire in the form of Google Form for data collection. The data processing procedures used include data collection, data reduction, data presentation, and drawing conclusions. The respondents involved were 60 students from the Mechanical Engineering Education study program, consisting of bachelor and master levels. The results of this research are that there are several factors that influence students in choosing a Mechanical Engineering Education study program, namely image, ambitions, job prospects, and interests. The interest factor influences the most, namely 18 students or around 30%, the image factor influences 13 students or around 21.6%, the ambitions factor influences 12 students or around 20%, and the job prospects factor influences 12 students or around 20%. A total of 5 students or around 8.3% chose a study program that was not according to their wishes or was forced to do so. All these factors positively influence students in choosing the Mechanical Engineering Education study program, because most students choose study programs because of their own wishes, while only a small percentage do not match their wishes.